The Effect of Duration of Laser Radiation with the Same Dose in the Treatment of Recurrent Aphthous Stomatitis - Farzaneh Aghakhani; Amir Mansour Shirani; Nima Amini (Isfahan University of Medical Sciences, 2022)
Recurring aphthous ulcers is a common and painful ulcer in the oral area. The aim of this study was to evaluate the impact of length of radiation in the same dose for the treatment of recurrent aphthous stomatitis. To date no similar study isavailable.Materials & Methods:In this double-blinded clinical trial, 30 patients with minor aphthous ulcer that were referred to Oral medicine department of Islamic Azad university were selected according to convenience sampling and inclusion exclusion criteria and were randomly divided into two similar groups. Low level laser therapy with diode 660nm was used in group A with 200 mW and 20 seconds setting and in group B with 20 mW and 200 seconds setting in two sessions on the first and third days were used. The time of clinical healing and the pain intensity as VAS were recorded. Data were analyzed by Independent t-test and Mann-Whitney test (p value < 0.05).Results:The pain intensity from first day after the laser until the seventh day in group B was significantly less than group A (p value < 0.001). The mean size of lesion was significantly lower in the third day (p value = 0.03), fifth (p value < 0.001) and seventh (p value = 0.001). The mean clinical healing time in group B was significantly lower than group A (p value < 0.001).Conclusion:According to this study's findings, longer time of irradiation in lower output power of 660 nm diode laser was suggested for treatment of recurrent aphthous ulcer